Combined microwave ablation and antiangiogenic therapy to increase local efficacy. Issue 2 (3rd March 2020) - Ni, Yang; Yang, Xia; Cui, Jian; Li, Zhichao; Yang, Pingping; Xu, Jiaju; Shan, Guanglian; Ye, Xin
Abstract: Purpose: We aim to evaluate the efficacy, safety and survival time of microwave ablation (MWA) with adjuvant antiangiogenic therapy-endostatin in animal models. Material and methods: A total of 40 rabbits successfully implanted with VX2 tumors were randomly assigned to four experimental groups: Group A underwent only microwave ablation of the tumors; Group B received only antiangiogenic drugs endostatin; Group C received endostatin immediately after MWA; Group D followed up without treatment. Results: Two months post-treatment, tumor sizes of Group A and Group C were reduced to 1.936 ± 0.373 cm 3 and 1.592 ± 0.382 cm 3, respectively. However, tumors grew to 15.091 ± 1.735 cm 3 and 47.825 ± 7.664 cm 3 in Group B and the control group. Three months post-treatment, tumor sizes in Group A and Group C maintained as 1.395 ± 0.394 cm 3 and 1.482 ± 0.305 cm 3, significantly smaller than Group B (35.277 ± 6.019 cm 3 ). All animals in the control group died, while four (40%) survived in Group B (Endo Group). The numbers of survivals in Groups A and C were seven (70%) and eight (80%), respectively. The lowest metastasis rate (2/10, 20%) was observed in Group C (combination therapy). Conclusion: The combination of MWA and antiangiogenic therapy triggered a significant reduction in the growth rate and metastases of tumors and may potentially improve survivals.